Metabolic and immune/inflammatory alterations induced by a triathlon under extreme conditions - Cesar Miguel Momesso Santos; Cesar Miguel Momesso Santos; Jônatas Bussador Amaral; Marcelo Rossi; Rodolfo Paula Vieria; Rodolfo Paula Vieria; Rodolfo Paula Vieria; Rodolfo Paula Vieria; Cesar Cavinato Cal Abad; Cesar Cavinato Cal Abad; André Luis Lacerda Bachi; André Luis Lacerda Bachi (Frontiers Media S.A., 2022)
PurposeTo investigate the effects of triathlon racing under extreme conditions on metabolic and immune/inflammatory responses.MethodsThirteen amateur athletes participated in an extreme triathlon competition (swim - 3.8 km; cycling - 180 km; running - 4 2 km; with a 3,700 m accumulated altitude). Blood samples were collected on three different occasions: pre-competition (baseline), immediately post-competition (IM), and 12 h post-competition (12 h) to evaluate glycemic and lipid profiles, leukocytes count, and cytokines levels in plasma and in whole-blood cell culture supernatant stimulated or not with LPS.ResultsDecreased glucose and triglycerides levels, increased LDL, and a significant leukocytosis were observed at IM and 12 h compared to baseline. In addition, higher serum levels of IL-6, IL-8, and IL-10 were found at IM than in baseline and post-12 h. Whereas increased IL-12p40 levels were observed for 12 h compared to baseline. At baseline, in LPS-stimulated cell culture, IL-6, IL-8, and IL-12p70 were higher, while IL-12p40 levels were lower than non-stimulated cell culture. At IM, IL-12p40 levels were unchanged, while higher levels of other cytokines were found in LPS-stimulated cell culture compared to non-stimulated cell culture. The 12 h results showed higher levels of IL-6, IL-8, and IL-10 in LPS-stimulated cell culture than in non-stimulated cell culture. Additionally, a significant negative correlation between circulating glucose levels and IL-6 was found.ConclusionThe triathlon competition's performance under extreme conditions has remarkable impacts on the lipid profile and systemic immune/inflammatory responses. For the first time, significant alterations in the cytokine responses of whole blood cell culture to LPS-stimulation in baseline, IM, and 12h were demonstrated.